Development of Cloud Computing Student Database Application Utilizing Google Workspace Education for Assessment of Guidance and Counseling Service Needs - Wahyu Nurhamzah; Ahmad Budi Sutrisno; Zam Immawan Alam; Andi Nurliana (PT Publikasiku Academic Solution, 2026)
The rapid development of information technology has transformed educational services, including guidance and counseling practices in vocational schools. However, the process of collecting, managing, and analyzing student data is still often conducted manually, resulting in inefficiency and less accurate needs assessment. Therefore, a cloud-based solution is required to support a more systematic and data-driven approach. This research aims to determine the level of need for a student database, develop a cloud computing-based student database application utilizing Google Workspace for Education, and evaluate its practicality, validity, and effectiveness in assessing guidance and counseling service needs. This research employed a R&D approach to design and test a prototype application. The data were collected through needs assessment, expert validation, and user trials involving guidance and counseling teachers and students in vocational schools. The results indicate that guidance and counseling teachers strongly need a cloud computing-based database system to facilitate student needs assessment. The developed prototype is capable of managing student data digitally, including personal data, assessment results, and profiles of guidance and counseling needs. Furthermore, the application meets the criteria of validity and practicality, and is proven effective in improving the efficiency of data collection and analysis, as well as supporting the development of data-based counseling service programs. In conclusion, the cloud computing-based student database application utilizing Google Workspace for Education is a practical, valid, and effective solution for optimizing the assessment of guidance and counseling service needs.